Profil Sustainability Consciousness Peserta Didik Fase C di Sekolah Jenjang Dasar Kabupaten Gresik - Asita Al Mufida; Husnuz Zuhad; Kartika Irene Widjanarko (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Sustainable Development Goals (SDGs) have become the focus of many scientists worldwide, with environmental, social, and economic aspects being the focus of these SDGs. However, achieving them requires a high level of Sustainability Consciousness, particularly among young learners. Therefore, this study examines the level of Sustainability Consciousness (SC) of elementary school students in Phase C. This study used a quantitative approach with a survey method. A questionnaire was developed with indicators of sustainability knowingness, sustainability attitudes, and sustainability behavior. Each indicator focuses on environmental, social, and economic aspects. The study involved 59 elementary school students in the Gresik area and its surroundings. The results of this study indicate that students' sustainability awareness (SC) is in the good category, both in the aspects of sustainability knowingness, sustainability attitudes, and sustainability behavior. Except for sustainability behavior in the economic aspect, students still have insufficient awareness of these indicators. Based on these results, it can be concluded that students' sustainability awareness is good; however, their empathy needs to be developed to enable them to participate in helping lower-middle-class communities, so that all members of society can collectively prepare themselves to support the achievement of sustainable development goals. It is hoped that the results of this study can serve as a basis for follow-up and serve as an initial reference for future research.